Documents and Shifting Labor Environments Among Undocumented Migrant Workers in Northern California (2016)
This article explores the ways in which migrant workers establish particular relations to the state in shifting environments of criminalization and stigmatization that change the geography and nature of undocumented labor in the United States. Centering on Northern California, I address the results of the economic downturn between 2007 and 2009 for undocumented migrant men who had established jobs and paid taxes using fake Social Security cards, but whose labor conditions became unsustainable, leading many of them to turn to informal labor sites. I argue that work environments for many migrants shift to effectively ensure the marginalization of cheap labor, while maintaining their contributions to local economies and accommodating to the political constraints of the moment. I follow accounts of counterfeit identification, mainly fake Social Security cards, in labor practices that inscribe migrant laborers into the “system” they are supposed to be abusing, but to which they actually contribute a great deal through mimetic articulations of citizenship. I show how severing such ties becomes necessary in times of economic crisis and heighted criminalization, and I illustrate the ways in which real and imagined state repression make what Nicholas De Genova (2002) has called “deportability” an effective way to control and maintain an undocumented labor force within the boundaries of the country. © 2016 by the American Anthropological Association